"Density equilibrium" method for the quantitative and rapid in situ determination of lipid, hydrocarbon, or biopolymer content in microorganisms - Eroglu, Ela; Melis, A. (John Wiley & Sons, 2009)
The work provides a simple method, based on a direct density equilibrium measurement, for the rapid in situ estimation of total lipid, hydrocarbon or biopolymer content in a variety of prokaryotic and eukaryotic samples. The method can be readily applied to live microalgae and photosynthetic bacteria, single-celled or colonial microorganisms, as well as cellular fractions and isolated subcellular compartments or components. In this approach, the absolute lipid, hydrocarbon, or biopolymer content of the cells can be readily calculated. This method is especially useful for tracking the oil or polymer content of strains of microalgae and other microorganisms, whose lipid, hydrocarbon or biopolymer content may change with cultivation conditions and/or time, as the case would be in microorganism lipid-induction industrial processes. The method is also useful for the direct in situ measurement of storage polymer accumulation in live cells, such as starch in microalgae and polyhydroxybutyrate, or other polyhydroxyalkanoates, in photosynthetic and non-photosynthetic bacteria.© 2008 Wiley Periodicals, Inc.